Power Doppler ultrasonography and synovitis: correlating ultrasound imaging with histopathological findings and evaluating the performance of ultrasound equipments. Issue 12 (17th May 2006) - Koski, J M; Saarakkala, S; Helle, M; Hakulinen, U; Heikkinen, J O; Hermunen, H
Abstract : Objectives: To examine the validity of power Doppler ultrasound imaging to identify synovitis, using histopathology as gold standard, and to assess the performance of ultrasound equipments. Methods: 44 synovial sites in small and large joints, bursae and tendon sheaths were depicted with ultrasound. A synovial biopsy was performed on the site depicted and a synovial sample was taken for histopathological evaluation. The performance of three ultrasound devices was tested using flow phantoms. Results: A positive Doppler signal was detected in 29 of 35 (83%) of the patients with active histological inflammation. In eight additional samples, histological examination showed other pathological synovial findings and a Doppler signal was detected in five of them. No significant correlation was found between the amount of Doppler signal and histological synovitis score (r = 0.239, p = NS). The amount of subsynovial infiltration of polymorphonuclear leucocytes and surface fibrin correlated significantly with the amount of power Doppler signal: r = 0.397 (p<0.01) and 0.328 (p<0.05), respectively. The ultrasound devices differed in showing the smallest detectable flow. Conclusions: A negative Doppler signal does not exclude the possibility of synovitis. A positive Doppler signal in the synovium is an indicator of an active synovial inflammation in patients. A Doppler signal does not correlate with the extent of the inflammation and it can also be seen in other synovial reactions. It is important that the quality measurements of ultrasound devices are reported, because the results should be evaluated against the quality of the device used.